2023
DOI: 10.1177/2046147x231165225
|View full text |Cite
|
Sign up to set email alerts
|

Examining the characteristics and virtues associated with servant leadership in public relations

Abstract: Are servant leadership and ethics of care being practiced by public relations leaders? This study involved in-depth interviews with 32 public relations leaders working in a variety of organizational settings in the United States and provided insights from men and women, including people of color. We found evidence of an “other oriented approach” to leadership that involved prioritizing the needs and concerns of employees and a genuine concern for the wellbeing of others. The findings are consistent with charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Findings, which are summarized in Table 2, underscored Neill and Meng's (2023) assertion of the importance and value of servant leadership, extending it empirically into the realm of internal crisis management. The importance of other-orientation and individual care and focus may not be possible in an acute, momentary crisis, but participants demonstrated that such care was often the most meaningful approach in an ongoing crisis.…”
Section: Theoretical Implicationsmentioning
confidence: 85%
See 1 more Smart Citation
“…Findings, which are summarized in Table 2, underscored Neill and Meng's (2023) assertion of the importance and value of servant leadership, extending it empirically into the realm of internal crisis management. The importance of other-orientation and individual care and focus may not be possible in an acute, momentary crisis, but participants demonstrated that such care was often the most meaningful approach in an ongoing crisis.…”
Section: Theoretical Implicationsmentioning
confidence: 85%
“…Scholars have emphasized a multitude of aspects, including the importance of listening and reflexivity (Willis, 2019), gender identity (e.g. Aldoory and Toth, 2004; Meng and Neill, 2022), flexibility and adaptability (Shin et al ., 2011) and servant leadership, an approach where “the leader is a servant first who places a priority on the needs of others” (Neill and Meng, 2023, p. 185). Leadership has a significant impact on employee satisfaction and engagement (Meng and Berger, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, research also suggests that the sense of empathy facilitates emotional healing, which does not only involve being sensitive to the personal concerns and well-being of others but also shows the willingness to take the time to address the concerns (Barbuto and Wheeler, 2006). Leaders who deliver a sense of empathy and exhibit emotional healing make themselves available to others, stand by them and provide them with support (Neill and Meng, 2023; ven Dierendonck, 2011). Thus, we argue that it is important to examine the potential outcomes of demonstrating the sense of empathy as part of the core characteristics associated with servant leadership in influencing the effectiveness of adaptive leadership processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ullah et al (2021) explored the mediating role of grit between servant leadership and job performance, proposing that grit should also be examined as a moderator in the relationship between the two concepts. Similarly, Neill et al (2023) propose the role of grit should be explord with different leadership approaches. Thus, we propose the following hypothesis: H3: Grit significantly moderates the relationship between servant leadership and job performance.…”
Section: Servant Leadership Grit and Job Performancementioning
confidence: 99%